Robust Product Designs, Part II: Second-Order Models - Jones, Stephen; Box, George (My University, 1990)
In this paper we apply the strategy developed in Report 56 to a general second-order model. For this model we derive the robustness measure and give a series of tables of designs that are appropriate for the possible objectives of the experimenter.